CFD simulation and validation of urban microclimate: A case study for Bergpolder Zuid, Rotterdam. (January 2015) - Toparlar, Y.; Blocken, B.; Vos, P.; van Heijst, G.J.F.; Janssen, W.D.; van Hooff, T.; Montazeri, H.; Timmermans, H.J.P.
Abstract: Considering climate change and the rapid trend towards urbanization, the analysis of urban microclimate is gaining importance. The Urban Heat Island (UHI) effect and summer-time heat waves can significantly affect urban microclimate with negative consequences for human mortality and morbidity and building energy demand. So far, most studies on urban microclimate employed observational approaches with field measurements. However, in order to provide more information towards the design of climate adaptive urban areas, deterministic analyses are required. In this study, Computational Fluid Dynamics (CFD) simulations are performed to predict urban temperatures in the Bergpolder Zuid region in Rotterdam, which is planned to be renovated to increase its climate resilience. 3D unsteady Reynolds-averaged Navier–Stokes (URANS) simulations with the realizable k – ε turbulence model are performed on a high-resolution computational grid. The simulations include wind flow and heat transfer by conduction, convection and radiation. The resulting surface temperatures are validated using experimental data from high-resolution thermal infrared satellite imagery performed during the heat wave of July 2006. The results show that the CFD simulations are able to predict urban surface temperatures with an average deviation of 7.9% from the experimental data. It is concluded that CFD has the potential of accurately predicting urban microclimate. Results from CFD simulations can therefore be used to identify problem areas and to evaluate the effect of climate adaptation measures in these areas such as urban greening and evaporative cooling. Graphical abstract: Highlights: Analysis of urban microclimate by 3D unsteady RANS CFD simulations. Validation of surface temperature simulation results based on satellite imagery data. Average deviation between simulation results and satellite imagery data is 7.9%. CFD has the potential of accurately predicting urban microclimate. Presented approach shows the effect of heat storage and flow field on temperatures.